The Effect of Cash Ownership on the Company's Performance in the Food and Beverage Industry Listed on the Indonesia Stock Exchange (IDX) - Agustyas Widianingsih; Prana Sri Surya Dewi; Farah Margaretha Leon (International Journal Labs, 2023)
This study was conducted to determine the relationship between the company's cash ownership and company performance linearly. The sample used for this study is companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. There are 20 companies that are sampled in this study purposively. To determine the company's performance, a ratio of ROA and ROE is used for comparison. In this study using regression methods and individual tests (t-tests). The results of this study show that cash ownership does not have a significant relationship with company performance. For future research, it is recommended to add variables that can support ROA and ROE that are not contained in this study and use a larger sample of data.